Chromatographic method for the determination of inflammatory biomarkers and uric acid in human saliva - Vernerová, Andrea; Krčmová, Lenka Kujovská; Heneberk, Ondřej; Radochová, Vladimíra; Strouhal, Ondřej; Kašparovský, Adam; Melichar, Bohuslav; Švec, František (Talanta, 2021)
Determination of concentration of biomarkers of the activation of immune system, uric acid, and creatinine in the saliva can be useful tool for the diagnosis and monitoring of early manifestations of diseases such as malignant, inflammatory, and periodontal disorders. We have developed and validated a high-performance liquid chromatographic method coupled with fluorescence and diode array detection for the separation and quantification of neopterin, tryptophan, creatinine, uric acid, and kynurenine in the human saliva. A separation of these analytes was achieved within 9 min by using second-generation monolithic stationary phase and elution with phosphate buffer. The present method involves very simple sample preparation requiring small amount of sample matrix. The internal standard 3-nitro-l-tyrosine was used for a more precise quantification. The sensitivity of the present method was demonstrated with lower limits of quantification of 0.6 × 10-3 μmol/L for neopterin, 0.725 μmol/L for tryptophan, 0.12 μmol/L for creatinine, 0.18 μmol/L for uric acid, and 0.135 μmol/L for kynurenine. The method was validated with 67 real-life saliva samples collected from patients suffering from breast, ovarian, colorectal, and renal cancer, and 19 saliva samples from patients with periodontal diseases and allowed monitoring of inflammatory response.
Keywords: sliny; Saliva; Chromatography, High Pressure Liquid; Kynurenine; biologické markery; kyselina močová; lidé; tryptofan; Humans; vysokoúčinná kapalinová chromatografie; Tryptophan; Biomarkers; Uric Acid; kynurenin